Comparison of Three Doses of Cytarabine Consolidation for Intermediate- and Adverse-risk Acute Myeloid Leukemia: Real World Evidence From Thai Acute Myeloid Leukemia Registry - Chanswangphuwana C. (2023)
Background: Intermediate or high doses of cytarabine (IDAC or HiDAC) were recommended as postremission chemotherapy for acute myeloid leukemia (AML). This retrospective study investigated the real-world outcomes of 3-different cytarabine doses from the multicenter Thai AML registry database. Patients and Methods: The intermediate- and adverse-risk AML patients (N = 258) who achieved complete remission and proceeded to single-agent cytarabine consolidation were enrolled. Results: The median relapse-free survival (RFS) using IDAC 1.5 g/m2, high-dose cytarabine (HiDAC) 2 g/m2, and HiDAC 3 g/m2 were 12.6, 11.7, and 13 months, respectively. The median overall survival (OS) using IDAC 1.5 g/m2, HiDAC 2 g/m2, and HiDAC 3 g/m2 were 34.9, 22.7, and 23.7 months, respectively. No significant difference in RFS and OS was detected between the 3 doses. Secondary AML, white blood cell > 100×109/L and the adverse-risk AML were independent prognostic factors for inferior survival (P= .008, P < .001, P= .014). Patients who completed 3 to 4 cycles of consolidation had significantly superior RFS and OS (P< .001, P< .001). Febrile neutropenia occurred in 72.9% of IDAC, 73.8% of HiDAC 2 g/m2, and 78.1% of HiDAC 3 g/m2 without statistical significance. However, the incidence of septic shock was significantly higher after HiDAC 3 g/m2 compared to IDAC regimen (8% vs. 3%, P= .037). Conclusion: IDAC is an appropriate regimen for postremission chemotherapy for intermediate- and adverse-risk AML. The higher dosing levels may not produce any benefits to patients and may increase incidence of septic shock. The number of consolidation cycles may impact on survivals rather than the intensity of cytarabine.